Renewable energy and local development: Seven lessons from the mining industry. Issue 1 (2nd January 2018) - Marais, Lochner; Wlokas, Holle; de Groot, Jiska; Dube, Noleen; Scheba, Andreas
ABSTRACT: Having long depended on fossil fuels for energy generation, South Africa is now investing in renewable energy. Like its mining operations, its renewable energy plants will have local implications. Renewable energy companies are therefore required by government to engage with communities to contribute to socio-economic development. We present seven lessons we believe the renewable energy sector can learn from the mining industry. We argue that the new industry must: manage social disruption, understand community complexities, create responsive institutions and the capacity to support industry practice, employ trained community practitioners, be clear about the aims of local development, encourage economic diversification in remote areas and, importantly, in view of problems caused by downscaling in the mining industry, plan for the possible closure of projects. Renewable energy projects could then serve and shape local development.